U-73122, a phospholipase C inhibitor, impairs lymphocytic choriomeningitis virus virion infectivity - Mizuma, Keita; Hashizume, Mei; Urata, Shuzo; Shindo, Keiko; Takashima, Ayako; Mizuta, Satoshi; Iwasaki, Masaharu (Journal of general virology, 2024)
Lassa virus (LASV) is an Old World (OW) mammarenavirus that causes Lassa fever, a life-threatening acute febrile disease endemic in West Africa. Lymphocytic choriomeningitis virus (LCMV) is a worldwide-distributed, prototypic OW mammarenavirus of clinical significance that has been largely neglected as a human pathogen. No licensed OW mammarenavirus vaccines are available, and the current therapeutic option is limited to the off-label use of ribavirin, which offers only partial efficacy. This situation underscores the urgent need to develop novel antivirals against human pathogenic mammarenaviruses. Previously, we showed that afatinib, a pan-ErbB tyrosine kinase inhibitor, inhibited multiple steps of the life cycles of OW LASV and LCMV, as well as the New World Junín virus vaccine strain Candid#1. In the present study, we investigated the inhibitory effect of U-73122, a phospholipase C inhibitor that acts downstream of ErbB signalling, on LCMV multiplication. U-73122 inhibited WT recombinant (r) LCMV multiplication in cultured cells. Preincubation of cell-free LCMV virions with U-73122 resulted in impaired virion infectivity. U-73122 also inhibited the infection of rLCMVs expressing heterologous viral glycoproteins, including the vesicular stomatitis Indiana virus (VSIV) glycoprotein, whereas WT VSIV infection was not affected by U-73122 treatment. Our results show the novel bioactivity of U-73122 as an LCMV inhibitor and indicate the presence of a virion-associated molecule that is necessary for virion infectivity and can be exploited as a potential antiviral drug target against human pathogenic mammarenavirus infections.